The relationship between umbilical cord blood IL-22 level and infantile eczema at 42 days - Lu, Xujun; Wang, Wenge; Wang, Yang; Huan, Chuo; Yang, Yue (Frontiers in Pediatrics, 2024)
【Background】The occurrence of eczema is related to helper T 22 (Th22) cytokine disorder, and Th22 mainly secretes interleukin-22 (IL-22). This study aims to investigate the predictive value of umbilical cord blood IL-22 levels on the onset of eczema in infants within 42 days. 【Study Design】The study selected 157 full-term healthy neonates born between September 2020 and May 2021. Cord blood was collected immediately after birth to determine IL-22 levels, and the infants were followed up for 42 days to assess the incidence of eczema. 【Results】Among the 157 infants who completed the 42-day follow-up, 86 developed eczema and 71 did not. The level of IL-22 in the umbilical cord blood of the eczema group was lower than that of the non-eczema group (p＜0.05). Additionally, the incidence of eczema in children whose Family history of allergy was significantly higher than in the group without eczema (p＜0.05). Logistic regression analysis revealed that low cord blood IL-22 levels were independent risk factors for eczema (p＜0.05). The ROC curve of cord blood IL-22 levels and infant eczema showed that the cut-off value is 36.362 pg/ml, the area under the curve (AUC) is 0.613, the standard error is 0.045, the 95% CI is 0.526-0.701, the sensitivity is 63.4%, and the specificity is 57.0%. Therefore, there is a certain correlation between cord blood IL-22 levels and the incidence of infant eczema. 【Conclusions】Low IL-22 levels in umbilical cord blood may be linked to the development of infant eczema within 42 days, indicating a potential predictive value, although this value appears to be limited.